Hedonic consumption experience in videogaming: A multidimensional perspective - Hollebeek, L.D. (Elsevier Ltd, 2022)
Prior research primarily considers consumers' hedonic gaming experience, defined as an individual's level of pleasure, emotional gratification, and enjoyment from playing a videogame, from a unidimensional perspective. However, given the growing range of technology-enabled, hedonic game-related (e.g., aesthetic, competition, or social) elements, we argue that this one-dimensional view is rapidly becoming dated. Correspondingly, we propose a broadened multi-dimensional perspective of videogamers' hedonic experience, as informed by hedonic consumption theory and the theory of planned behavior. Using a sample of 294 gamers, our results confirm the existence of gamers' multi (i.e., seven)-dimensional hedonic consumption experience comprising escapism, fantasy, role-projection, emotional involvement, enjoyment, arousal, and sensory experience. We also find that gamers' emotional involvement, enjoyment, arousal, and sensory experience, in particular, drive their attitude formation toward a videogame, in turn impacting users' videogaming intent and behavior. We conclude by discussing implications that arise from our research. Â© 2021 Elsevier Ltd